2019
DOI: 10.1111/pcn.12824
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation rates during long‐term, second‐generation antipsychotic long‐acting injection treatment: A systematic review

Abstract: Aim The aim of this review was to analyze the discontinuation rates during long‐term treatment with second‐generation antipsychotic long‐acting injection (SGA‐LAI) in adults with either schizophrenia spectrum or bipolar disorders. Methods A systematic search (PubMed, Scopus, and the Cochrane Library) of studies published in English (1 January 2001–12 October 2018) identified 1214 abstracts, which were analyzed independently by the author and two colleagues. Studies were retrieved and reviewed if they reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Antipsychotic treatment results in a good response soon after the first episode, but are associated with low clinical and social recovery rates (around 13.5%) (33). This is due to various factors, as poor treatment adherence tends to establish in most patients in the long run [even with long-acting injectable antipsychotic drugs (LAIs), premature treatment termination is more than 50% (34)] and, even when adherence is ensured, after long-term treatment, 15% of patients will still show symptoms of chronic illness (35). Clearly, the management of illness requires constant care for symptom control, relapse prevention, and psychosocial long-term rehabilitation (3), but mainly focuses on drug treatment, mostly antipsychotic drugs (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic treatment results in a good response soon after the first episode, but are associated with low clinical and social recovery rates (around 13.5%) (33). This is due to various factors, as poor treatment adherence tends to establish in most patients in the long run [even with long-acting injectable antipsychotic drugs (LAIs), premature treatment termination is more than 50% (34)] and, even when adherence is ensured, after long-term treatment, 15% of patients will still show symptoms of chronic illness (35). Clearly, the management of illness requires constant care for symptom control, relapse prevention, and psychosocial long-term rehabilitation (3), but mainly focuses on drug treatment, mostly antipsychotic drugs (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…The commonest reason for medication discontinuation in both was patient choice and not inefficacy. Retrospective studies of antipsychotic LAIs generally have a greater discontinuation rate than prospective (randomized or open label) studies at 1 year, as observed in a recent descriptive review, 14 with retrospective studies being more representative of clinical reality. A discontinuation rate of aripiprazole LAI at 1 year of 25% was reported in 2 prospective randomized studies 10,15 and 1 prospective open label study 16 .…”
Section: Discussionmentioning
confidence: 92%
“…The commonest reason for medication discontinuation in both was patient choice and not inefficacy. Retrospective studies of antipsychotic LAIs generally have a greater discontinuation rate than prospective (randomized or open label) studies at 1 year, as observed in a recent descriptive review, 14 with retrospective studies being more representative of clinical reality. A discontinuation rate of aripiprazole LAI at 1 year of 25% was 20 ; and 27%, Anderson et al 21 Higher 1-year discontinuation rates in retrospective studies are also reported, however, for aripiprazole LAI: 66% in schizophrenia and 64% in bipolar disorder, 22 and for paliperidone LAI: 61%, 23 and a 2-site study in Holland 69% and in Belgium 77%, with apparent stability of rate over different periods sampled.…”
Section: Discussionmentioning
confidence: 92%
“…Systematic reviews between SGA-LAIs and FGA-LAIs have focused on mortality risk 41 or discontinuation rates. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews between SGA-LAIs and FGA-LAIs have focused on mortality risk 41 or discontinuation rates. 42 A more recent systematic review and meta-analysis focused on efficacy and safety found only three trials (n = 459) with direct comparisons of SGA-LAIs versus FGA-LAIs, two of them on psychiatric hospitalizations, concluding for no significant differences between them. 40 In a 12-month open-label rater-blinded RCT, number of hospitalizations were not significantly different between patients (n = 54) receiving LAIrisperidone (31 mg mean monthly dose) and TherapeuTic advances in psychopharmacology those receiving haloperidol-LAI (114 mg mean monthly dose) or fluphenazine decanoate (37 mg mean monthly dosage) in 54 patients.…”
Section: Discussionmentioning
confidence: 99%